Performance analysis and environmental assessment of small-scale waste biomass gasification integrated CHP in Iceland. (15th April 2020) - Safarian, Sahar; Unnthorsson, Runar; Richter, Christiaan
Abstract: Integrated waste biomass gasification with cogeneration heat and power (CHP) is an attractive method for high efficiency electricity generation. It not only involves wastes as fuel but also helps in reduction of releasing pollutant gasses to the atmosphere. In this research, a simulation model is developed to assess performance and environmental impacts of producing electricity from gasifying of organic wastes in Iceland: garden, timber/wood, and paper mixed wastes. The objectives are to find the optimal operating conditions to make the highest electrical efficiency and the evaluation of global warming (GWP), acidification (AP) and eutrophication (EP) potentials in regard to the environmental impact of the system. Moreover, the environmental assessment for the integrated waste gasification and CHP is compared with waste incineration in a conventional and currently running system. Our results show that the electricity production from waste gasification technology appears to be more environmentally friendly than waste direct combustion in all impact categories considered. Among the systems, timber and wood waste is the most beneficial from performance and environmental perspectives. The 1 kW h electricity production from timber through gasification would lead to a GWP of 0.07 kg CO2 eq, AP of 0.09 kg SO2 eq, and EP potential of 0.36 kg NO3 eq. Graphical abstract: Image 10469 Highlights: Suggestion of waste gasification as a sustainable solution for waste disposal in Iceland. Development of a simulation model for waste gasification integrated with CHP. Finding of optimal operating conditions for highest electrical efficiency. Comparison of waste gasification and incineration in terms of 3 environmental impacts. Environmental assessment of producing electricity from gasifying of organic wastes.